Relationships between safety climate factors and occupational safety and health level of awareness in Malaysia Government Agencies / Abu Hanipah Ramli - Abu Hanipah, Ramli (2014)
Construction work is dangerous and it is essential that safety of workers be guaranteed. Safety studies in the public sector are limited compared with the private sector. This study surveyed the influence of safety climate and adoption of OHSAS 18000 on safety of construction supervisors in the Department of Irrigation and Drainage (DID) Malaysia, the Public Works Department, Malaysia (PWD), and the Rescue and Fire Department, Malaysia (FRDM). A methodology is developed in diagnosing the Level of Awareness (LoA) on Occupational Safety and Health which includes questionnaire design, observation, data collection, statistical analysis, multiple-regression analysis and model validation. One-hundred-sixty-four personnel took part in the survey from DID, one-hundred and four from PWD and one-hundred and six from FRDM. The mean work experience for DID was 14.1 years, for PWD was 17.4 years and for FRDM was 10.5 years. Management commitment, employee participation, training and education and communication were tested. Level of Awarenes included safety orientation, company policy, monitoring, risk assessment and review. Data were collected using self-administered questionnaire. Anova tests were applied to data collected. Regression analysis showed that for DID communication was the most significant factor influencing safety among construction supervisors. Results showed there were significant influences of management commitment, employee participation and training and education on LoA. Results also showed work experience had a significant influence on LoA. Designation, education level and age had no significant influence on LoA. The adoption of OHSAS 18000 did not seem to result in any marked enhancement in LoA of OSH Management. The developed model was then validated by testing the significant factors namely communication, training and education, employees’ participation and management commitment on two other different government agencies namely PWD and FRDM. PWD is a supervisory agency doing similar jobs with DID and FRDM is an agency doing work which is more towards rescue. Regression analysis showed that for both PWD and FRDM, communication was the most significant factor influencing LoA among front liner personnel. Results showed in both PWD and FRDM, there were significant influences of management commitment, employee participation and training and education and communication on LoA. Results also showed work experience had a significant influence on LoA. Designation, education level and age had no significant influence on LoA. These results highlight that Communication, Training and Education, Employee Participation and Management Commitment are the predicted factors in the study of LoA on OSH Management for government agencies and also for private companies in Malaysia.